A prime q divides both n 2 + 3 and n 2 + 2 n + 4 for some integer n .
The remainder when n is divided by q is r . Find q + r .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To elaborate on what you're doing in the first half of the solution (and disspelling some of the magic that seems to be happening), essentially you are looking for polynomial combinations of n 2 + 2 n + 4 , n 2 + 3 that will give a linear term. In such a case, using the euclidean algorithm gives us a deterministic process, as opposed to having to "guess" at how to eliminate n . We have
( n 2 + 2 n + 4 ) 4 ( n 2 + 3 ) − ( n 2 + 3 ) − ( 2 n − 1 ) ( 2 n + 1 ) = = 2 n + 1 1 3
Hence, ( − 2 n + 1 ) ( n 2 + 2 n + 4 ) + ( 2 n + 3 ) ( n 2 + 3 ) = 1 3 .
Note: The identity
q
(
4
m
+
2
k
−
k
2
q
)
=
1
3
in the solution translates into
4
(
n
2
+
3
)
+
2
(
(
n
2
+
2
n
+
4
)
−
(
n
2
+
3
)
)
−
(
(
n
2
+
2
n
+
4
)
−
(
n
2
+
3
)
)
2
=
1
3
,
When carefully expanded, this does indeed lead to the equation
(
−
2
n
+
1
)
(
n
2
+
2
n
+
4
)
+
(
2
n
+
3
)
(
n
2
+
3
)
=
1
3
.
@Calvin Lin Thanks
Problem Loading...
Note Loading...
Set Loading...
Since q ∣ n 2 + 3 and q ∣ n 2 + 2 n + 4 ⇒ q ∣ 2 n + 1 ⇒ 2 n + 1 = k q . . . ( 1 ) , where k is integral.
Also q ∣ n 2 + 3 ⇒ n 2 + 3 = m q . . . ( 2 ) , where m is integral.
Eliminating n in Equations ( 1 ) and ( 2 ) gives 4 m q + 2 k q − k 2 q 2 = 1 3 ⇒ q ( 4 m + 2 k − k 2 q ) = 1 3 ⇒ q ∣ 1 3 ⇒ q = 1 3 .
Now ( 1 ) and ( 2 ) may be rewritten as congruences:
2 n ≡ − 1 ( m o d 1 3 ) and n 2 ≡ − 3 ( m o d 1 3 ) . Solving both simultaneously yields n ≡ 6 ( m o d 1 3 ) i.e r = 6 .
Thus q + r = 1 9 .